1992
DOI: 10.1017/s0025315400059440
|View full text |Cite
|
Sign up to set email alerts
|

Trophic structure within the Bristol Channel: seasonality and stability in Bridgwater Bay

Abstract: A general description of the trophic inter-relationships and the food web within Bridgwater Bay, Somerset, England, is presented. This Bay is a lower estuarine site within the Bristol Channel. Particular attention is given to the use of the area by fish and larger crustaceans which are the dominant animal groups. Using data collected over a ten-year period of monthly sampling, the relative average biomass of all fish and larger crustaceans found within the Bay is calculated for each month of the year. These av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 46 publications
(35 reference statements)
2
43
0
Order By: Relevance
“…Finally, Gadiform abundance in autumn was included in the spring model and negatively related to Crangon crangon abundance. Despite including whiting Merlangius merlangus, a very abundant and important predator of brown shrimp (Henderson & Holmes 1989, Henderson et al 1992, Hamerlynck & Hostens 1993, Singh-Renton & Bromley 1999), Gadiforms did not show a significant cross-correlation with the Dutch Wadden Sea shrimp abundances, contradicting the observations in the German area (Siegel et al 2005) and in the Bristol Channel (Henderson et al 2006). However, the abundance of Gadiforms was correlated with the abundance of other predators especially Scorpaeniforms.…”
Section: Factors Affecting Spring Abundancementioning
confidence: 84%
See 2 more Smart Citations
“…Finally, Gadiform abundance in autumn was included in the spring model and negatively related to Crangon crangon abundance. Despite including whiting Merlangius merlangus, a very abundant and important predator of brown shrimp (Henderson & Holmes 1989, Henderson et al 1992, Hamerlynck & Hostens 1993, Singh-Renton & Bromley 1999), Gadiforms did not show a significant cross-correlation with the Dutch Wadden Sea shrimp abundances, contradicting the observations in the German area (Siegel et al 2005) and in the Bristol Channel (Henderson et al 2006). However, the abundance of Gadiforms was correlated with the abundance of other predators especially Scorpaeniforms.…”
Section: Factors Affecting Spring Abundancementioning
confidence: 84%
“…d -1 ) of brown shrimp (CRANG) and potential predators grouped at Order level were then extracted from the database and mean daily abundances were determined for each season (see below). The potential predators included Clupeiforms (CLUP), Gadiforms (GAD), Perciforms (PERC), Scorpaeniforms (SCORP), Pleuronectiforms (FLAT) and Decapods (CRAB) (Tiews 1970, De Vlas 1979, Pihl 1985, Henderson & Holmes 1989, Henderson et al 1992, Hamerlynck & Hostens 1993, Berghahn 1996, Cattrijsse et al 1997). …”
Section: Biological Time Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since estuaries are highly productive ecosystems (Schelske & Odum, 1970) and thereby facilitate the rapid growth of juvenile fish, it is relevant that the inshore shallows of the Oldbury region contain high densities of small crustaceans, which are an important food source for juvenile fish in the region (Moore & Moore, 1976;Moore et al, 1979;Henderson et al, 1992). The important role played by the shallows of the Severn Estuary as a nursery ground for certain marine species parallels the situation recorded in temperate estuaries elsewhere in the Northern Hemisphere and also in the Southern Hemisphere (e.g.…”
Section: Faunal Composition Of the Inner Estuarymentioning
confidence: 99%
“…Several studies by Henderson and co-workers (e.g. 385 Henderson, 1989;Henderson et al, 1992) have shown how potentially useful power plant catches can be utilized to advance scientific knowledge on carrying capacity, niche occupation and trophic structure, and in the process, to give good advice pertaining to power plant siting and operations.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%